Detection of Human Cytomegalovirus in Colorectal Adenocarcinoma by In Situ Hybridization Technique - Abdulla Mukhlis, Faiza (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Human Cytomegalovirus (HCMV) infects a wide range of human cells, including colonic epithelial cells that give rise to adenomas and adenocarcinomas. Persistent productive infection of tumor cells is essential for oncomodulation by HCMV.This study aimed to detect HCMV matrix protein using in situ hybridization technique (ISH) in colorectal adenocarcinoma compared to normal colon tissues, and to the presence of cytomegalovirus inclusion bodies in infected colorectal carcinomas. Patients and methods: Twenty six of colorectal adenocarcinomas were obtained in paraffin-blocks compared to 10 normal colon specimens which were age and sex matched as control group. Detection of HCMV was obtained by in situ hybridization technique. Results:The biotinylated probe specific for DNA encoded HCMV-matrix protein showed hybridization with nucleic acid in 20 cases out of (26) of colorectal adenocarcinomas representing (76.9%) compared to normal colon tissue which revealed no hybridization signals. Moderate to high scoring signals were detected in moderate to poorly differentiated groups. Inclusion bodies were detected in 11 (42.3%) cases with positive hybridization signals. Conclusion: HCMV may play a role in the colorectal adenocarcinoma pathogenesis. In situ hybridization test are considered the most sensitive and specific tools for detection of HCMV DNA in tissues. Epidemiological, histopathological identification of cytomegalic inclusion bodies and molecular studies are necessary to confirm the association of HCMV and colorectal tumorogenesis in Iraqi population.